Stretchable, Antifreezing, Non‐Drying, and Fast‐Response Sensors Based on Cellulose Nanocomposite Hydrogels for Signal Detection. Issue 12 (23rd September 2021) - Zhang, Wei; Ma, Chang; Huang, Ling‐Zhi; Guo, Wen‐Yan; Li, Dan‐Dan; Bian, Jing; Ma, Ming‐Guo
Abstract: Conductive hydrogels have received widespread attention in the applications of biosensors, human–machine interface, and health recording electrodes. Herein, the conductive hydrogels integrated with antifreezing, water retention, reusable, and sensing performances are fabricated by introducing polyvinyl alcohol, cellulose nanofibril, MXene nanosheets, and glycerol. The as‐prepared hydrogels present prominent electrical conductivity (2.58 mS cm −1 ) and flexibility even at −18 °C. In addition, the hydrogels have favorable water retention performance and can reuse after heating and cooling. When used as sensors, the hydrogels illustrate high sensitivity (gauge factor of 2.30), fast response time (0.165 s), wide working strain range (559%), favorable linearity ( R 2  = 0.999), and wide operating temperature range (−18 to 60 °C). The hydrogels can detect not only large strains of 10–200%, but also small strains of 1–5%, making them promising candidates for wearable sensors to monitor large and subtle movements. Abstract : The conductive hydrogels integrated with antifreezing, water retention, biocompatibility, reusable, and sensing performances are achieved by introducing polyvinyl alcohol, cellulose nanofibril, MXene nanosheets, and glycerol. The as‐prepared hydrogels present prominent flexibility and conductivity even at −18 °C. When used as sensors, the hydrogels can detect not only large strains, but also small strains and illustrate fast response time (0.165 s).